IMPROVING ELDERLY HEALTH STATUS THROUGH HEALTH EDUCATION WITH RANDOM BLOOD GLUCOSE SCREENING AMONG ELDERLY MEMBERS OF GKJW SEMAMPIR CONGREGATION - Akde Triyoga (Pedagogic Research-Applied Literacy Journal, 2025)
Implementation of improving elderly health status through health education using the random blood glucose screening at GKJW Semampir Congregation, Kediri showed that 20% of the elderly had started to suffer from Elderly Diabetes, and 60% of the elderly were healthy. The elderly need to maintain their health by regulating a healthy diet, physical activity that is appropriate for the elderly and maintaining stress and elderly life. In the elderly group, education and training need to be provided in compiling a food menu that can prevent Diabetes Mellitus and physical activities that are safe and appropriate for the elderly.